PROTECTION OF FOREIGN INVESTMENTS AND ARBITRATION PROCEEDINGS: TRENDS OF RECENT YEARS - Togzhan Yessenbayeva (Modern American Journals, 2025)
The article examines the evolutionary stages of the development of international investment arbitration, as well as key mechanisms for the protection of foreign investors, including the investor-state dispute settlement (ISDS) system. Particular attention is paid to the contemporary transformation of arbitration practice, driven by criticism of the lack of transparency in procedures, the high cost of proceedings, and interference with the regulatory sovereignty of states. Reform initiatives, including the project of a Multilateral Investment Court (MIC), aimed at increasing the legitimacy and effectiveness of the system, are analyzed. Illustrative arbitration cases are presented, demonstrating the pursuit of a balance between the protection of investors and the safeguarding of public interests. The work contributes to a deeper understanding of current trends in international investment protection and the legal regulation of investment relations.
Keywords: Foreign investments, international arbitration, investment disputes, international public law, investor protection, ISDS, investment treaties.